Analysis of the Agropolitan Area Development in the Sumber sub-district, Probolinggo Regency in 2020 - Erna - Haryanti (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2021)
The research, entitled Analysis of the Agropolitan Area Development in the  Sumber sub-district, Probolinggo Regency in 2020 aims: (1) To analyze the potential development of production centers and programs in the Agropolitan Area in Sumber Sub-district (2) To analyze facilities and infrastructure need for developing agropolitan areas in the sub-district Sumber for 5 years (3) Determine the strategy for developing agropolitan areas in the Sumber Sub - district. Samples or informants were selected by purposive sampling method that  consists of: (1) Regional Government, (2) group of farmers working on superior commodities, (3) marketing institutions in agropolitan areas. The data analysis method is divided into three models, namely (1) SWOT analysis, (2) Mapping production centers and superior commodities, (3) agropolitan area development strategy.The results of the research are (1) The leading commodities in the agropolitan area of the Sumber sub-district are potatoes, carrots, cabbage, leeks and dairy cows. The priority villages are Ledokombo and Pandansari. The agropolitan area development program is an increase in the production of food crops, horticulture and animal husbandry, increased processing of products, increased marketing and increased institutional support, (2) the conditions of production transportation , marketing and infrastructure facilities are not good, (3) agribusiness area development strategy is to optimize the strength / potential that is owned to take advantage of the opportunities available Keywords—: Development Strategy; Agropolitan; SWOT analysis